UKRAINIAN LITERARY THEORY PERCEPTION OF STANISLAV PSHYBYSHEVSKY’S MODERNIST IDEAS - Ткачук , Т. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the logic and dynamics of the reception S. Pshybyshewsky’s modernist ideas in Ukrainian literary criticism after 1909. It is noted that individualism, voluntarism, the concept of a strong personality, the doctrine of the innovations of the symbolist drama, the image-symbol are the main correlates of the innovations of the Polish writer, most demanded among the Ukrainian literators in the XXth century. The article uses the archive materials of Nathan Kachka, which have not been analyzed in the Ukrainian literary criticism till present days.